Pengembangan Modul Biologi Berbasis Integrasi Al-Quran: Identifikasi dan Pemanfaatan Tumbuhan Obat Tradisional di Sibuhuan Kecamatan Barumun Sebagai Sumber Belajar di SMA - Hasibuan, Fadlya Purnama; Rahmadina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
The research aims to develop a biology module based on the integration of the Quran on the identification and utilization of traditional medicinal plants in Sibuhuan, Barumun District as a learning resource in high schools. The research method uses Research and Development with the ADDIE model. The analysis stage identifies medicinal plants through field exploration and interviews with local communities. The design stage designs the module framework. The development stage conducts expert validation. The implementation stage applies the module with a pretest-posttest. The evaluation stage analyzes the effectiveness of learning. Data were obtained through observation, interviews, validation questionnaires, and learning outcome tests using expert validation instruments, student and teacher response questionnaires, and pretest-posttest tests. Data were analyzed descriptively quantitatively by calculating validity, practicality, and effectiveness scores using the N-Gain test. The results showed that the module successfully identified four main medicinal plant species: guava leaves, papaya leaves, siropas para leaves, and sambung nyawa. The module was declared highly valid by media and material experts, highly practical according to students and teachers, and effective based on the increase in student understanding from pretest to posttest. The developed module effectively improved students' conceptual understanding, strengthened the integration of Al-Quranic values ​​in biology learning, and preserved the local wisdom of the Sibuhuan community as an authentic learning resource. This research contributes to the development of biology learning that integrates Islamic values ​​and local wisdom.